The Effect of Price, Promotion and Location in the Shopee Marketplace on Purchasing Decisions of SDID Customers with Purchase Intention as a Mediating Variable - Sri Nathasya; Reynaldi Pramudita Subakti (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
SDID is a company operating in Surabaya City, East Java, Indonesia that specializes in dental and oral health supplies. The company sells a wide range of products, from professional dental equipment to general oral care items, such as toothbrushes and mouth sanitizers. Through the Shopee marketplace platform, SDID reaches consumers online, making the store one of the top choices for professionals and people who need quality dental health products in Surabaya and surrounding areas. The purpose of this study was to determine the effect of price, promotion, and location on purchase intention, determine the effect of price, promotion, and location on purchasing decisions, determine the effect of purchase intention on purchasing decisions, and determine the effect of purchase intention as a mediating variable on the effect of price, promotion, and location on purchasing decisions on the Shopee marketplace at the SDID store. This study has a sample size of 200 respondents who are dentists or dental experts, have made purchases at SDID at least once with a nominal purchase of more than or equal to IDR 300,000. The method in this study is quantitative, with analysis using Partial Least Square - Structural Equation Model (PLS-SEM). This study shows that price, promotion, and location have a significant and positive effect on buying interest in the Shopee marketplace at the SDID store. Furthermore, price, promotion, and location have a significant and positive effect on purchasing decisions on the Shopee marketplace at the SDID store. Then, buying interest has a significant and positive effect on purchasing decisions on the Shopee marketplace at the SDID store. Finally, buying interest is able to mediate the relationship between price, promotion, and location on purchasing decisions at the Shopee marketplace in the SDID store.